The Potential of Diving in Teluk Dalam Banjarmasin City - Lazuardy Akbar Fauzan; Alitya Putra Maulidan; Eka Purnama Indah; Maria Agnesia Panggabean; Mutia Kastaniah; Muhammad Adlian Ashafiq (UNIB Press, 2023)
Diving is a sport that requires skill, courage and agility in jumping from a great height into water. Teluk Dalam District is an area that has facilities and infrastructure for diving practiceApart from that, in this area, especially around the river, you can find many children happily playing in the river, such as swimming, diving, jumping from higher places and so on. The aim of this research is to determine the potential of diving in society Teluk Dalam District Banjarmasin City. This research method uses a descriptive quantitative approach. Data was obtained from tests using the sport search method. The population of this study were elementary school students in Teluk Dalam District. The results of this research were that 21 students or 10.0% had an interest in the first choice of diving, and 10 students or 4.8% were identified as having potential talent. In the second choice there were 20 students or 9.6% and 7 students or 3.3% were identified as having potential talent.